2009
DOI: 10.1001/archsurg.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Overweight on Patients With Gastric Cancer After Undergoing Curative Gastrectomy

Abstract: Being overweight is not a poor risk factor for survival in patients with gastric cancer, although it is independently predictive of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 41 publications
(21 reference statements)
2
54
3
1
Order By: Relevance
“…8,10,12,21 Similarly, the definitive implications of overweight in Western patients with gastric cancer have yet to be determined due to the paucity of data for the association between BMI and prognosis. 22 Using a well defined multi-institutional data set from a Western country, the present study demonstrated that overweight was associated with a significant survival benefit by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,12,21 Similarly, the definitive implications of overweight in Western patients with gastric cancer have yet to be determined due to the paucity of data for the association between BMI and prognosis. 22 Using a well defined multi-institutional data set from a Western country, the present study demonstrated that overweight was associated with a significant survival benefit by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Several authors have already reported that overweight increases the incidence of general and intra-abdominal complications in Asian patients undergoing gastrectomy for gastric cancer. [5][6][7][8][9][10][11][12] Some recent studies also suggested that obesity may correlate with long-term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In general, patients with gastric cancer tend to be cachexic with low BMIs as gastric cancer progresses to more advanced stages because such patients tend to have gastrointestinal symptoms such as epigastric pain, nausea, and anorexia, particularly in gastric outlet obstruction. Previous studies have shown significant decreased prevalence of T3-4 or N2-3 category cancer in patients with BMI C 25 kg/m 2 , although some studies have provided no relationship between BMI and the stage of gastric cancers [48,49]. Previous studies suggesting a relationship between obesity and gastric cancers have generally ignored weight change from tumor progression and enrolled patients without considering the stage of their tumor.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reasons behind our figures converging toward that level. One is the comparatively high rate of multivisceral resections and another may be a high median BMI (25.2); this has been defined as a risk factor for anastomotic leakage in gastric surgery [29,30]. Based on current clinical evidence it is difficult to define a causal relationship between POPF and anastomotic complications when the procedures do not involve the pancreatic gland per se.…”
Section: Discussionmentioning
confidence: 99%